PUBLICATION AND INVENTIVE ACTIVITY OF SCIENTIFIC UNIVERSITIES: SAINT-PETERSBURG NATIONAL RESEARCH UNIVERSITY OF INFORMATION TECHNOLOGIES, MECHANICS AND OPTICS - Shegelman I. R., Vasilyev A. S. (Pedagogical experience: from theory to practice, 2019)
the indicators of publication and inventive activity of scientists of the St. Petersburg National Research University of Information Technologies, Mechanics and Optics (ITMO), who ranked seventh among the best universities in Russia according to the Forbes rating, are given.
Keywords: интеллектуальная собственность; объекты интеллектуальной собственности; патент; индекс Хирша; цитирование; наукометрические показатели; публикации; результаты интеллектуальной деятельности; intellectual property; scientometric indicators; база знаний; publications; knowledge base; patent; Hirsch index; objects of intellectual property; intellectual results; citation